PENGGUNAAN METODE PROBING-PROMPTING UNTUK MENINGKATKAN KEMAMPUAN BERBICARA SISWA - Syiami, Nur Fitri (2015)
Mata pelajaranbahasaJepangmemilikiperanan yang sangatpentingdalammewujudkanketerampilansiswadalamberbicarabahasaJepang.MenurutTarigan, (2008, hlm.16) berbicaraadalahsuatualatuntukmengkomunikasikangagasan-gagasan yang disusunsertadikembangkansesuaidengankebutuhan-kebutuhan sang pendengarataupenyimak. Namunfaktanya, tidaksedikitsiswa yang merasatidakpercayadiri, gugupdankesulitanberbicarabahasaJepang.Olehsebabitu, penulisbermaksudmenggunakanmetodeiniuntukmemudahkansiswadalampembelajaranberbicarabahasaJepang.TujuanpenelitianiniadalahuntukmengetahuipenggunaanmetodeProbing-Prompting dalammeningkatkankemampuanberbicarabahasaJepang. Selainitu, untukmengetahuitanggapansiswamengenaipenggunaanmetodeProbing-Prompting.Metode yang digunakandalampenelitianiniadalaheksperimenkuasi. Desainpenelitiannyaadalahone group pretest-posttest design.Sampelpenelitiannyaadalahsiswakelas XI Bahasa SMAN 1 Rancaekek yang berjumah 16 orang.Instrumenpenelitianiniadalahtesdanangket.Hasilanalisis data, diperolehnilai mean pre-test adalah 4,5dannilai mean post-test adalah 9,0625.Dengandemikianterdapatpeningkatansetelahdiberikanperlakuan (trearment) yaitusebesar 4,5625. Dan didapatkannilaithitungdarinilai pre-test dan post-test sebesar 17,7051dengandb=15. Dengandemikiandapatdisimpulkanbahwathitung>ttabel(17,7051 > 2, 95) untuktarafsignifikan 1%.SehinggadapatdisimpulkanbahwaHkdapatditerima.Data tersebutdapatmenegaskanbahwaterjadipeningkatankemampuanberbicarabahasaJepangsebelumdansesudahdilaksanakannyatreatment..Berdasarkanhasilangket, penggunaanMetodeProbing-Prompting jugadikatakandapatmenambahkeberaniansiswadalamberbicaradanjugadapatmembantumeningkatkankemampuanberbicarasiswa.BerdasarkanhalinimakametodeProbing-Prompting dapatdijadikansebagaisalahsatubagiandarimetode yang dapatditerapkanuntukmeningkatkankemampuanberbicarabahasaJepangsiswadi kelas. Kata kunci :Metode Probing-prompting, Kemampuan berbicara, Eksperimen Kuasi The lesson of Japanese language has a very important role to interpret student's skill in Japanese language speaking. According to Tarigan (2008, p.16) Speaking is a tool to communicate the ideas which are arranged and developed based on the listeners need. However the fact, there are many students lack of self-confidence, nervous and difficult to speak Japanese. That's why the writer intend to use this method to make the students easier to learn speaking Japanese language. The main goals of this research are to know the usage of the Probing-Prompting Method to increase the student ability in conversation learning. Beside that to know the student responses about the implementation of this method in learning process. The method which is used in this research is Quasi Experiment. The design is used is one group pretest-posttest design. The object of the research is the 11th graders students of language class at SMAN 1 Rancaekek which amounts 16 students. The research used test and questioner as instrument. The data analysis are achieved that the average of pre-test is 4,5 and the average of post-test is 9,0625. So that there is increasing after doing treatment 4,5625. The researcher got the value t score from the pre-test and post-test as much as 17,7051 in db = 15. It can be concluded that t score > t table with 17,7051>2,95 for signification 1%. We can conclude that Hk can be acceptable. The data can be stated that student ability in Japanese speaking after doing treatment can increase significantly. Based on questioner result, the usage of probing-prompting method can make the student brave to speak Japanese and can increase student's ability in Japanese speaking. It means that probing-prompting method can be the one of methods which must be applied in learning Japanese speaking skill at class. Keywords : Probing-prompting method, speaking ability